Design of a Sustainable Mini Rotary Dryer for Organic Rice Farmers - Akhmad Fadli Ibrahim; Yuvita Satriani Djuli; Jeki Jeki; Aldin Pratama; Hasbiadi Hasbiadi (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2025)
The drying process of harvested grain is critical for maintaining quality and preventing spoilage. Traditional sun-drying methods are inefficient and highly dependent on weather conditions, resulting in inconsistent yields and potential losses. This study aimed to design and construct a mini rotary dryer as an effective and efficient tool for drying grain, specifically designed for organic rice farmers. A rotary dryer prototype was built and tested to reduce the moisture content of 50 kg of freshly harvested grain from 50% to 13.7% within 8 hours. Energy consumption, including electricity and gas usage, was monitored to evaluate operational cost efficiency. The results showed that the rotary dryer reliably achieved the target moisture content with a total operational cost of IDR 13,076, equivalent to approximately IDR 261.5 per kilogram of dry grain. Compared with traditional drying, the rotary dryer significantly reduces drying time and dependence on weather while maintaining consistent drying quality. The developed mini rotary dryer provides a practical and economically feasible solution to improve post-harvest processing for organic rice farmers. This study contributes to sustainable agricultural practices by optimizing drying technology suitable for small-scale farming.